Sustainable design of pipelines : guidelines for achieving advanced functionality - Schwarz, Walt; White, Patrick (Civil engineer); Mihm, Mark S. (American Society of Civil Engineers, 2022)
"MOP 151 details the sustainable design and construction of pipelines and presents methods, practices, and decisions that influence and guide sustainable planning, design, construction, and operation, including the Envision infrastructure sustainability rating system"-- Provided by publisher
Keywords: Pipelines -- Design and construction.; Sustainable construction.; elektronické knihy; electronic books